Intolerance of Uncertainty-Related Aspects of Planning for the Future During the Pandemic - Hromova, Hanna (Journal of Education Culture and Society, 2022)
Thesis. The ability to set long-term goals is associated with lower levels of Intolerance of Uncertainty (IU), but the pandemic has interrupted the established planning strategies. This study aims to clarify the differences in the planning horizons before and during the pandemic for people with different levels of IU. Methods. The study was conducted in March-April 2021. 120 respondents filled in Intolerance of Uncertainty Scale, short form (IUS-12), Zimbardo Time Perspective Inventory (ZPTI) and answered two additional questions about the duration of the planning period. Then comparison and correlation analyses were conducted. Results. Respondents with different levels of IU also differ in terms of their Time Perspective (TP) profiles. During the pandemic, average planning horizons became shorter for all respondents. The subgroup with low IU showed that planning is associated with the present TP scales. There was a direct association between attitudes towards the Future and planning horizons in the subgroup with average IU level. Planning horizons associated with Past Negative and Present Fatalistic TP were present in the group with high IU level. Conclusion. During the pandemic, levels of IU and planning horizons have shown an inverse relationship. The pandemic and inability to plan in advance in a habitual way primarily affect people who tend to feel confused in conditions of uncertainty and insecurity, that is, people with high scores on the Inhibitory Anxiety scale in the IU questionnaire. Peculiarities of how the planning strategies change in subgroups with different levels of IU before and during the pandemic are discussed.